Konstrukcja prawna planowania przestrzennego w Polsce w latach 1945–1989 - Woźniak, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The main objective of this paper is to present the legal construction of the spatial planning in Poland between 1945 and 1989, as well as its evaluation from the perspective of the development of spatial planning and management legislation. The thesis put forward in the paper is that between 1945 and 1989, i.e. in the years when the principle of self-governance was not supported by state institutions, spatial planning was detached from the needs of local communities. Analyzing the legal construction of the spatial planning in Poland between 1945 and 1989 showed a certain regularity, namely that the spatial order construction was difficult at that time due to the then socio-economic conditions resulting in the centrally controlled spatial development and a hierarchy of spatial planning acts. The paper indicates that in those years, there was a connection between spatial planning and building law, but it was not as strong as in the interwar period. The connotations with the environmental law in turn manifested themselves in the downplaying of environmental issues in spatial planning. The article shows that in the years 1945–1989, there was little interest from the legislator in the category of public interest, which at the time became known as “social interest”.
Keywords: legal construction; spatial planning; public interest; hierarchy of planning acts